PERSEPSI SISWA TERHADAP IMPLEMENTASI E-LEARNING DALAM PEMBELAJARAN BAHASA SUNDA - Aini, Dianisa; Kosasih, Dede; Nugraha, Haris Santosa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to analyze and identify students' perceptions of the implementation of E-Learning in Sundanese language learning at SMP Alfa Centauri, Bandung. This study uses a qualitative descriptive method, by conducting interviews and distributing questionnaires to students involved in the use of E-Learning. With a total of 177 students from grades VII and VIII. The data sources taken from this study are primary and secondary data. The sampling technique used the probably sampling technique. This study revealed that most students agree with the existence of E-Learning because it is considered an effective means of delivering material, a fun learning process and helps improve students' skills and motivation in learning Sundanese. Although there are some technical challenges such as difficulty in accessing E-Learning caused by poor internet, school services are very helpful for every difficulty experienced by students, and other problems are that students feel that interacting with teachers is more enjoyable directly. The features in E-Learning are very easy for students to understand, this is also supported by adequate technology. Every student already has a gadget or laptop so that it supports the learning process. However, there needs to be an evaluation in the use of E-Learning, both evaluations of teachers or students, because some students still do not understand the skills in using technology. This study has limitations in terms of the number of samples due to the limitations of Sundanese teachers and students, so the results may not fully describe broader perceptions.